Collective bargaining practices in Eastern Europe: Case study evidence from Romania - Aurora Trif (Max Planck Institute for the Study of Societies, 2005)
There are several studies on recent developments in collective bargaining in Eastern Europe, but there is still a debate about the extent to which collective bargaining practices resemble those in continental Western Europe. This paper aims to contribute to this debate, by examining primary data on collective bargaining practices in Romania using an actor-centred institutionalist approach. It focuses on collective bargaining in four large chemical companies. Comparisons are made to other countries in order to highlight the developments in Romanian cases. Unexpectedly, the study's findings point to an increase in state intervention in establishing the terms and conditions of employment after 1989, due to the state's new roles during the transformation process that affected job security. The study suggests a considerable increase in the influence of top managers in determining pay and working conditions, while trade unions retained the considerable influence over social benefits in large companies. The findings show continuance of certain pre-1989 practices, such as a persistence of high state intervention and a limited independence of the trade unions from the management. This paper contributes to a deeper understanding of institutional changes in the context of a shift from a centrally planned economy to a market-based economy. – – Trotz einer Vielzahl von Studien über die Entwicklungen der Tarifverhandlungen in Osteuropa in den letzten Jahren herrscht Uneinigkeit darüber, inwieweit die osteuropäischen Verhandlungspraktiken mit den westeuropäischen übereinstimmen. Dieses Papier trägt zu dieser Debatte bei, indem es die Ergebnisse empirischer Analysen von Tarifverhandlungen in Rumänien auf der theoretischen Grundlage des akteurzentrierten Institutionalismus analysiert. Die Untersuchung konzentriert sich auf vier Großunternehmen der chemischen Industrie. Es werden Vergleiche zu anderen Ländern gezogen, um die Entwicklungen in den rumänischen Fallbeispielen hervorzuheben. Unvorhergesehenerweise zeigen die Untersuchungsergebnisse, dass nach 1989 staatliche Eingriffe in der Bestimmung der Arbeitsbedingungen zugenommen haben. Dies ist auf die neuen Aufgaben des Staates zurückzuführen, die dieser während des Transformationsprozesses im Bereich der Beschäftigungssicherung übernommen hat. Die Studie zeigt einen merklichen Anstieg der Einflussnahme des Topmanagements auf Tarif- und Arbeitsbedingungen, während Gewerkschaften im Bereich der Sozialleistungen in großen Unternehmen einen weiterhin großen Einfluss ausüben. Die Ergebnisse deuten auf eine Weiterführung bestimmter Praktiken hin, die vor 1989 üblich waren, wie zum Beispiel die starke staatliche Intervention sowie die begrenzte Unabhängigkeit der Gewerkschaften vom Management. Dieses Working Paper trägt zum besseren Verständnis des institutionellen Wandels im Rahmen des Wechsels von einer Zentral- zu einer Marktwirtschaft bei.
Keywords: 300